Performance Analysis and Automatic Prototype Aquaponic of System Design Based on Internet of Things (IoT) using MQTT Protocol - Ratnasih Ratnasih; Doan Perdana; Yoseph Gustommy Bisono (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2018)
The Aquaponic is a farming system which need attention because their system will mutually influence each other. Then using IoT technologies, can be made aquaponic that can automatically control and monitoring the aquaponic. The prototype using nodeMCU as a microcontroller, and for communication the system using MQTT protocol and android application as a user interface. The purpose of this research is to provide convenience for aquaponic user to be able to control remotely. In addition, this research aim is to analysis the QoS performance of the prototype. This research uses 2 scenario testing, there is with changing the distance between sensor nodes and access point, and testing the system in a normal state. Based on the results of the testing that has been done, the farther the distance range of the sensors node with access point then declining system performance. But in the normal state test, the median value of the mean delay was 0.10512s and the median value average throughput was 566 Bytes/s. In addition the median value also obtained the mean availability and realibility system that is 98.258% and 98.204%. Refers to the standard TIPHON (DTR/TIPHON-05001), the QoS performance of this system include excellent category.